Effect of Water Absorption on Some Electrical and Dielectrical Properties of Epoxy Resin Reinforced with Chopped Carbon Fibers - Jafar, H I; Husaen, S I; Al-Ajaj, E A (Al-Nahrain Journal of Science, 2011)
In this research, we study a.c electrical conductivity (σa.c ( ) and dielectric properties (dielectric constant (έ), and dissipation factor ( tanδ) ), with frequency change (102 -107 Hz) for the epoxy resin and composites reinforced with chopped carbon fiber ,prepared by hand lay –up method (EP +5% CF), (EP +10% CF), (EP +15% CF), (EP +20% CF), Were measured electrical conductivity of epoxy and composites with frequency change and at room temperature the results showed a.c electrical conductivity dependence with frequency relationship σ (ω)=Aωs to the values of the exponential factor (s)of less than one all samples, and adopted the theory of filtration for the interpretation of data conductivity for composites reinforced with carbon fibers was selected epoxy+20% C.F showed a higher electrical conductivity (13.6 * 10-7 (ohm.cm)-1). The composites were immersed in water at room temperature for 6, 10,15,20,27 days. The results showed that the electrical conductivity of (σ (ω)) increasing with increasing weight gain(M%) due to water absorption. Itwas found that dielectric constant increases when the percentage moisture absorption increase, whereas dielectric constant (έ) is dependent on capacity of composite materials.